2021
DOI: 10.1186/s12885-020-07769-2
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue masses: distribution of entities and rate of malignancy in small lesions

Abstract: Background Small soft tissue masses are often falsely assumed to be benign and resected with failure to achieve tumor-free margins. Therefore, this study retrospectively investigated the distribution of histopathologic diagnosis to be encountered in small soft tissue tumors (≤ 5 cm) in a large series of a tertiary referral center. Methods Patients with a soft tissue mass (STM) with a maximum diameter of 5 cm presenting at our institution over a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…Gassert et al recently investigated small soft tissue masses with a diameter <5 cm in a large patient series from a tertiary referral center and confirmed that a considerable proportion of small tumors were malignant (22.4%) (9). However, despite their importance, MRI features and demographic characteristics related to small malignant soft tissue tumors are not well established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gassert et al recently investigated small soft tissue masses with a diameter <5 cm in a large patient series from a tertiary referral center and confirmed that a considerable proportion of small tumors were malignant (22.4%) (9). However, despite their importance, MRI features and demographic characteristics related to small malignant soft tissue tumors are not well established.…”
Section: Discussionmentioning
confidence: 99%
“…The biologic potential of the tumors was dichotomized into benign and malignant according to the 5th edition of the World Health Organization (WHO) classification of soft tissue tumors (10). In the analysis of intermediate tumors, locally aggressive tumors that show local infiltration and destruction but do not metastasize were categorized as benign, whereas rarely metastasizing tumors that are often locally aggressive and have the potential to metastasize were categorized as malignant (9,11).…”
Section: Reference Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RMST depends on a multitude of other parameters. Such discrepancy in establishing the sarcoma diagnosis, however, evidences an unmet need in the work-up of sarcoma patients [ 9 ]. It may be helpful to agree on a common definition as to how to analyze biopsies to allow the comparison among multidisciplinary teams (MDTs).…”
Section: Discussionmentioning
confidence: 99%
“…In another study made in the Rhone-Alpes region in France (Lurkin et al 2010) [ 8 ], to evaluate the concordance between initial diagnosis and central pathology review for sarcoma cases, out of 366 patients diagnosed with sarcoma over a period of 1 year, 199 (54%) had full concordance between primary diagnosis (first pathologist) and second opinion (expert center pathologist), 97 (27%) had partial concordance (identical diagnosis of conjunctive tumor, but different grade or subtype), and 70 (19%) had complete discordance (different histological type or invalidation of the diagnosis of sarcoma). Another study (Gassert, F.G et al) [ 9 ] analyzed retrospectively the histopathologic findings of 1753 patients presenting with a soft tissue lesion ≤5 cm. They found that 22.4% of these lesions were malignant.…”
Section: Introductionmentioning
confidence: 99%